The Use of Artificial Intelligence (AI) in Food Logistics Systems to Support Global Halal Certification: A Systematic Literature Review - Trianita, Andhini Putri; Nurmalasari, Enny (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The development of Artificial Intelligence (AI) has reshaped global food logistics systems, particularly in strengthening halal certification integrity through enhanced transparency, operational efficiency, and traceability. The increasing global demand for halal products requires supply chains capable of ensuring end-to-end Sharia compliance. This review synthesizes findings from 20 international studies on the application of AI in halal food logistics using a Systematic Literature Review (SLR) method, with data collected from reputable journals, conference proceedings, and scientific repositories. The results indicate that integrating AI with technologies such as blockchain, the Internet of Things (IoT), and machine learning improves real-time supply chain monitoring, contamination risk prediction, and certification process automation. However, key challenges remain, including technological readiness, cross-border regulatory alignment, data security, and stakeholder integration. This study proposes a conceptual framework for AI implementation in global halal logistics and highlights future research directions to support sustainable and reliable halal supply chain systems.